On Character - Margot, Jean-Paul (Estudios de Filosofía, 2003)
In a seminar on Kant’s article answer on the question: what is Enlightenment? Habermas puts the problem of modernity in terms of consciousness of the discontinuity of time whereas Foucault does so in terms of Ethos, thus resuming a long tradition rooted in Aristotle and Theophrastus that ends, in a way, with La Bruyère.